2021
DOI: 10.3390/ijms222111817
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis Enterotoxin Upregulates Matrix Metalloproteinase-7 Expression through MAPK and AP-1 Activation in Intestinal Epithelial Cells, Leading to Syndecan-2 Release

Abstract: Bacteroides fragilis enterotoxin (BFT) produced by enterotoxigenic B. fragilis (ETBF) causes colonic inflammation. BFT initially contacts intestinal epithelial cells (IECs) and affects the intestinal barrier. Although molecular components of the gut epithelial barrier such as metalloproteinase-7 (MMP-7) and syndecan-2 are known to be associated with inflammation, little has been reported about MMP-7 expression and syndecan-2 shedding in response to ETBF infection. This study explores the role of BFT in MMP-7 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In contrast, we further explored the roles of ETBF, NTBF, and BFT in the integrity of the intestinal mucosal barrier. Jeon et al [ 26 ] revealed that BFT secreted by ETBF facilitated the upregulation of MMP-7 and release of syndecan-2 in intestinal epithelial cells, which disrupted the intestinal mucosal barrier. Similar results have been reported by Patterson et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we further explored the roles of ETBF, NTBF, and BFT in the integrity of the intestinal mucosal barrier. Jeon et al [ 26 ] revealed that BFT secreted by ETBF facilitated the upregulation of MMP-7 and release of syndecan-2 in intestinal epithelial cells, which disrupted the intestinal mucosal barrier. Similar results have been reported by Patterson et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 For example, fragilysin secreted by Bacteroides fragilis, a Gramnegative anaerobic bacterium, stimulates the expression of IL-8, TGFβ, and C5a, causing an inflammatory environment. 33 Besides, B. fragilis adjusts the imbalance of T-helper 17/T regulatory (Th17/Treg) cells, helping to maintain the intestinal immune microenvironment. 34 Further, Fusobacterium nucleatum causes an immunosuppressive environment through NK cell inactivation, reduction of T cell…”
Section: Gut Microbiome and Inflammationmentioning
confidence: 99%
“… 198 In a mouse model of CRC, enterotoxin Bacteroides fragilis (ETBF) stimulated the immune response through T helper 17 cells (Th17) and promoted colon tumor growth. 137 , 138 , 199 Similarly, E. coli expressing the genomic island polyketide synthase (pks+) enhanced tumorigenesis in preclinical CRC models and were found to be enriched in human CRC tissues . 200 , 201 Furthermore, pks + E. coli produces the genotoxin colibactin, which alkylates DNA, resulting in the formation of DNA adducts (a form of potentially mutagenic DNA damage) in colonic epithelial cells.…”
Section: Mechanisms By Which Human Carcinogenic Microbiomes Promote C...mentioning
confidence: 99%
“…This recruited CD8+ T cells and induced an inflammatory response, which damaged the gastric mucosa and promoted gastric carcinogenesis 198 . In a mouse model of CRC, enterotoxin Bacteroides fragilis (ETBF) stimulated the immune response through T helper 17 cells (Th17) and promoted colon tumor growth 137,138,199 . Similarly, E. coli expressing the genomic island polyketide synthase (pks+) enhanced tumorigenesis in preclinical CRC models and were found to be enriched in human CRC tissues 200,201 .…”
Section: Mechanisms By Which Human Carcinogenic Microbiomes Promote C...mentioning
confidence: 99%